INFRARED REFLECTOGRAPHY USE IN TATTOO REGISTRATION OF PARACAS-NECRÓPOLIS MOMIAS - Maita Agurto, Patricia (2013)
An exploration of the skin of twelve Paracas mummies using infrared reflectorgraphy has permitted the record of permanent cultural changes of the skin by tattoos. Infrared reflectography is typically used in the analysis of artwork, in particular to discover traces and designs hidden under paint layers. When used in mummies, the technique allows recording hidden tattoos. In many cases recording Paracas tattoos is difficult because the funerary treatment and bad preservation have camouflage tattoos, which are seem like blue or black stains in the skin. Results show characteristic of the Paracas skin modification that has never been registered before, such as pattern distribution of tattoos in the bodies and designs had been used for corporal decoration.